STUDI POPULASI Macaca fascicularis DI TAMAN WISATA HUTAN KERA TIRTOSARI KOTA BANDAR LAMPUNG - Derry Chandra Wijaya; Sugeng P. Harianto; Gunardi D. Winarno (Lambung Mangkurat University-Indonesia, 2018)
Macaques Forest Tourism Park is a green open space area that in 2007 was prepared as a resort where there are macaques there. TWHK was a habitat for macaques which lied in the middle of Bandar Lampung city. This research was conducted to determine the number of indivudual population of macaques, sex ratio and age range as well as the factors that impact the populations. This research used concentration count and interview method towards people around the research location during July 2017, from 7 o’clock in the morning till the evening. The research used habituation. The concentration count method was conducted in 3 locations where macaques often seen. There were 53 individuals of macaques. The macaques sex ration and age range for old male macaques were 8 individuals, old female macaques were 16 individuals, teens/ young macaques were 24 individuals, and baby macaques were 5 individuals. The comparison of sex ratio between adult males and females is 1: 2 individualsTaman Wisata Hutan Kera (TWHK) merupakan suatu kawasan ruang terbuka hijau yang pada tahun 2007 di persiapkan sebagai kawasan objek wisata dalam hal ini satwa M. fascicularis. TWHK merupakan habitat bagi M. fascicularis yang ada di tengah kota bandar lampung. Penelitian ini dilakukan untuk mengetahui jumlah populasi, sex ratio dan struktur umur serta faktor yang berpengaruh terhadap populasi M. fascicularis. Digunakan metode terkonsentrasi dan wawancara kepada masyarakat sekitar pada penelitian M. fascicularis selama bulan Juli 2017, pada pagi hari pukul 07.00 hingga sore hari. Penelitian dilakukan dengan melakukan habituasi. Metode concentration count dilakukan di tiga lokasi pengamatan yang paling sering dijumpai M. fascicularis. Populasi M. fascicularis di TWHK Tirtosari adalah 53 individu yang diperoleh dari data terbanyak dilapangan. Sex ratio dan struktur umur M. fascicularis untuk jantan dewasa 8 individu, betina dewasa 16 individu, remaja/anak-anak 24 ekor, dan bayi 5 individu. Perbandingan antara jantan dewasa dan betina dewasa adalah 1 : 2 individu.